Booty Capitalism : The Politics of Banking in the Philippines - Hutchcroft, Paul D. (Quezon City, 1998)
As discussed below, was to seek an explanation for the country's longstanding difficulties in converting its enormous developmental assets into sustained develop-mental progress.
Keywords: Capitalism - Philippines; Philippines - Economic Conditions